Effect of Induction Training Program on Teachers’ Effectiveness at Elementary School Level in Punjab - Khadija Butt, Muhammad Shahid Farooq (PJE, 2023)
Induction training is a support process for beginning teachers to teach them basic knowledge, skills, and values related with teaching and make them socialize with their profession. This study was conducted to explore effect of induction training program on Elementary School Educators’ (ESEs) teaching effectiveness. Ex-post facto research design was used for this quantitative study. Population comprised ESEs who received induction training from a public sector training academy at Provincial Headquarter Punjab-Pakistan and sample comprised of 331 ESEs.